2020
DOI: 10.1186/s13018-020-01599-5
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic ankle fusion only has a limited advantage over the open operation if osseous operation type is the same: a retrospective comparative study

Abstract: Background: A great deal of research suggests that arthroscopic ankle fusion (AAF) has advantages over open ankle fusion (OAF), but these outcomes would be imprecise because of a selection bias. The purpose of this study is to verify which is better for ankle fusion, AAF or OAF. We regrouped the OAF group into two subgroups according to whether the osseous operation type is the same as AAF group. The goal is to minimize the impact of disease severity, thereby reducing selection bias to some extent. Methods: We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…After the elimination of duplicates (n = 32), another 343 studies were excluded based on abstract and another 10 studies based on full-text assessment (see Supplementary File S4 for more information regarding excluding studies). A total of 13 studies [11,[14][15][16][28][29][30][31][32][33][34][35][36] were therefore included in the present review on the effectiveness of open-ankle arthrodesis vs. arthroscopy on our primary outcome (i.e., fusion rate).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the elimination of duplicates (n = 32), another 343 studies were excluded based on abstract and another 10 studies based on full-text assessment (see Supplementary File S4 for more information regarding excluding studies). A total of 13 studies [11,[14][15][16][28][29][30][31][32][33][34][35][36] were therefore included in the present review on the effectiveness of open-ankle arthrodesis vs. arthroscopy on our primary outcome (i.e., fusion rate).…”
Section: Search Resultsmentioning
confidence: 99%
“…The risk-of-bias scores of included studies are reported in Figure 2 both traffic light and summary plots. A total of 13 studies were analyzed [11,[14][15][16][28][29][30][31][32][33][34][35][36]. Figure 2A,B summarizes the risk of bias on fusion rate outcome.…”
Section: Risk-of-bias Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 , 10 Despite the many technologies proposed for ankle arthrodesis, it is frequently associated with comorbidities including hindfoot arthritis, delayed or nonunion, tibial stress fractures, infection, and compromised wound healing, which can subsequently result in a prolonged period of hospitalization and rehabilitation. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%